New Chemistry Insecticide Seed Treatments to Control Hessian Fly, Mayetiola destructor - Hill, Kurtis; Schwarting, Holly; Whitworth, Jeff (My University, 2017)
The Hessian fly (HF), Mayetiola destructor (Say), has been a periodical pest in Kansas for the past 100+ years (Dean and McCulloch, 1915). Plant resistance and insecticide seed treatments are the best and most consistent grower-controlled management tools and conventional insecticide seed treatments have been very effective (Wilde et al. 2001). However, new chemistries are periodically needed to retard resistance and it must be determined if these new chemistries are as effective as those that are commercially available. The treatments tested in this experiment did not provide effective or acceptable control of HF larvae. Because the HF is an important pest of wheat worldwide, the development and screening of these new insecticides will help Kansas wheat producers as well as wheat producers in all wheat producing regions of the world (Stuart et al., 2012).